The Strengthening of the Double Degree of Jurisdiction with the Advent of Law No. 13,467/17: Changes in Labor Law regarding the Appeal Deposit (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
The article analyzes the changes introduced by Law No. 13,467/2017 in article 899 of the CLT, focusing on the legal nature and new rules of the appeal deposit. The authors discuss the replacement of cash deposits with bank guarantees or judicial guarantee insurance, in addition to exemptions and value reductions for non-profit entities, micro-entrepreneurs, and companies in judicial recovery. It is concluded that the changes aim to guarantee access to the double degree of jurisdiction, balancing the guarantee of the court with the financial viability of companies. (Received: July 2025 | Accepted: September 2025)
Keywords: Appeal Deposit; Labor Reform; Double Degree of Jurisdiction